FAKTOR FAKTOR YANG MEMPENGARUHI PENDAPATAN INDUSTRI GENTENG DI DESA PEJATEN KECAMATAN KEDIRI KABUPATEN TABANAN - NI L PT BUDIARI; I WAYAN SUARBAWA; PUTU YUNDA DAMAYANTI (GANEC SWARA, 2024)
The purpose of this study is to determine the partial and simultaneous influence of capital, labor, and working hours on the income of the tile industry in Pejaten Village, Kediri District, Tabanan Regency. The sample size of tile entrepreneurs studied using a census technique amounted to 42 entrepreneurs. Data analysis was conducted using the multiple linear regression method. Based on the results of SPSS calculations, it was found that capital, labor, and working hours partially have a significant positive effect on the income of the tile industry in Pejaten Village, Kediri District, Tabanan Regency, with the regression function Y = 79,132,221.694 + 56,721.048X1 + 36,182.962X2 + 13,685.501X3. From the estimation results of the model, the calculated F value is 49.254 and the sig F value is 0.000 with an F table value of 2.85. Since the calculated F value is greater than the F table value (49.254 > 2.85) and the sig F value (0.000 < 0.05), it means that the variables of capital, labor, and working hours simultaneously have a significant effect on the income of the tile industry in Pejaten Village, Kediri District, Tabanan Regency. R2 = 0.895 indicates that 89.5% of the variation in income (Y) can be explained by the variation in capital, labor, and working hours, while the remaining 10.5% is explained by other variables not mentioned in this research model. Based on the data analysis, it can be concluded as follows: Capital, labor, and working hours have a significant positive effect partially on the income of the tile industry in Pejaten Village, Kediri District, Tabanan Regency. Capital, labor, and working hours have a significant simultaneous effect on the income of the tile industry in Pejaten Village, Kediri District, Tabanan Regency